INDEPENDENT CLASSES OF STUDENTS OF PHYSICAL CULTURE AND SPORTS - О.А. Permyakov; O.V. Porokhnenko; V.I. Marchyk (Academy of Cognitive and Natural Sciences, 2002)
Regular physical self-training and going in for sports are characteristic of a small number of students. Enhancing knowledge in theory and methods of teaching physical training, and transferring skills in planning students' time will enable them to increase both their interest in physical self-training and the number of those who go in for sports.